Pemberdayaan Keluarga Nelayan Melalui Pengolahan Ikan Asap untuk Produksi Bajabu Abon Khas Bugis Makassar di Pulau Karanrang Kabupaten Pangkajene - Dewi Andriani; Syahrul Mustafa; Sherry Adelia (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to empower fishermen's families in Karanrang Island through fish processing to produce Bajabu shredded typical of Bugis Makassar. The service method used initial observation, assistance with partner conditions, field data collection, and implementation of alternative solutions for product creation and evaluation. The service partners were a group of fishermen from Karanrang Island. This service created a product in the form of a Fish Smoking House (FSH) made entirely of stainless steel. It also created the Bajabu product, a roasted shredded Bugis Makassar delicacy packed and labeled for increased marketability.